A Tower of Tangled Histories: The Upper Silesia Tower in Poznań and the Making of an Unromantic Poland, 1911–1955. Issue 3 (2020) - Babiracki, Patryk
Abstract : Engaging with regional, international, and spatial histories, this article proposes a new reading of the twentieth-century Polish past by exploring the vicissitudes of a building known as the Upper Silesia Tower. Renowned German architect Hans Poelzig designed the Tower for the 1911 Ostdeutsche Ausstellung in Posen, an ethnically Polish city under Prussian rule. After Poland regained its independence following World War I, the pavilion, standing centrally on the grounds of Poznań's International Trade Fair, became the fair's symbol, and over time, also evolved into visual shorthand for the city itself. I argue that the Tower's significance extends beyond Posen/Poznań, however. As an embodiment of the conflicts and contradictions of Polish-German historical entanglements, the building, in its changing forms, also concretized various efforts to redefine the dominant Polish national identity away from Romantic ideals toward values such as order, industriousness, and hard work. I also suggest that eventually, as a material structure harnessed into the service of socialism, the Tower, with its complicated past, also brings into relief questions about the regional dimensions of the clashes over the meaning of modernity during the Cold War.